(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The present study investigated the phenolic compounds like tannin and flavonoids that provide banana peel extracts their antibacterial properties against bacterial pathogens, i.e., Enterobacter. aerogenes, Pseudomonas. aeruginosa, Salmonella. typhimurium, Staphylococcus aureus and Bacillus subtilis by using HPLC (High-performance liquid chromatography). The pathogenic bacteria affect skin (S. aureus), soft tissues, gastrointestinal tract (P. aeruginosa) and urinary tract (E. aerogenes) etc. Banana (Musa paradisica) peels at different stages of ripening (unripe, ripe, leaky ripe) were treated sequentially with 70% acetone, which was partitioned in order of polarity with water, ethyl acetate, chloroform, and hexane. Textural properties of fruit peel were determined by texture analyzer. The antibacterial activity of the samples was evaluated by the agar cup diffusion method, and inhibitory concentrations were measured by the MIC (minimum inhibitory concentration) method. The approach of formulating new drugs through natural sources has proved to be the most successful strategy. Many active metabolic products with biological significance are obtained from them. The findings of the present investigation suggested that the unripe banana peel sample had higher antibacterial activity than the ripe and leaky ripe (over-ripe). Higher MIC were obtained with water fractionate and 70% acetone extracts of banana peel against gram-negative bacteria, E. aerogenes and P. aeruginosa. Water fractionate has the highest inhibitory activity against gram-negative bacteria (E. aerogenes and P. aeruginosa) compared to gram-positive bacteria (S. aureus and B. subtilis). The ethyl acetate, chloroform and hexane fractionate of unripe, ripe and leaky ripe banana peels do not exhibit antibacterial activity. The highest concentration of tannin in unripe banana peels is one of the responsible phenolic components for its antibacterial activity. While certain flavonoids also exhibit antibacterial activity in banana peel, as the ripening proceeds. The present study discusses the essential information on banana peel, including its varieties, effect of ripening, solvent condition, pharmacological actions, and relevance in pharmaceutical industries. Banana peels, like tannin and flavonoid, exhibit broad-spectrum antimicrobial properties against all tested bacterial strains. Most of the compounds are polar in nature and water gives optimum conditions for extraction of these compounds from banana peel. It has the potential to be a nutraceutical preparation alternative and is beneficial to the pharmaceutical sector by providing the alternative of chemically synthesized drugs.